IMPROVED DIFFERENTIAL RELAY PERFORMANCE FOR A THREE-PHASE TRANSFORMER UNDER FAULT CONDITIONS - A. Akande, Adejare; Nyebuchi Amadi, Engr. Dr. Hachimenum; Horsfall, Engr. Dr. Dan; Okpara Uwho, Engr. Kingsley (Journal of Engineering and Technology (JET), 2025)
This research investigates the use of Differential Relay Systems to enhance protective measures for a 15.75/330 kV, 165 MVA power transformer at the Afam Power Generating Station, focusing on mitigating risks associated with overvoltage incidents. Overvoltage poses significant threats to transformer reliability, leading to insulation breakdown, core saturation, and overheating, jeopardizing operational stability and lifespan. The study proposes an improved protection system that utilizes differential relays. Differential relays effectively detect faults by comparing incoming and outgoing currents, identifying discrepancies indicative of faults. The differential relay system achieved a Mean Square Error (MSE) response of 0.03, demonstrating high accuracy in fault signature detection. The differential relay functions as a reliable protector, offering real-time response capabilities. By detecting minute differences between currents in the transformer windings, the relay ensures swift isolation of faults, thereby minimizing potential damage and preserving the integrity of the electrical system. The assessment of the differential relay's performance, alongside MSE calculations, provides a comprehensive understanding of the fault detection system's overall efficiency. This methods amplifies system reliability, fortifying it against emerging faults and optimizing response times to prevent critical incidents. This study marks a significant advancement in transformer protection methodologies, aiming to improve electrical grid reliability and stability through enhanced fault detection and predictive maintenance strategies. The findings underscore the effectiveness of this integrated approach in bolstering the resilience and operational efficiency of power transformers and the wider electrical grid infrastructure.